Finnish Trial on Practices of Anterior Cervical Decompression and Fusion (FACADE): A protocol for a prospective randomised non-inferiority trial comparing outpatient versus inpatient care - Kimmo Lönnrot; Simo Taimela; Pirjo Toivonen; Pasi Aronen; Anniina Koski-Palken; Janek Frantzen; Ville Leinonen; Marja Silvasti-Lundell; Johannes Förster; Teppo Jarvinen; FACADE investigators (BMJ Publishing Group, 2022)
Introduction
Although a great majority of patients with cervical radiculopathy syndrome can successfully be treated non-operatively, a considerable proportion experience persistent symptoms, severe enough to require neurosurgical intervention. During the past decade, cervical spine procedures have increasingly been performed on an outpatient basis and retrospective database analyses have shown this to be feasible and safe. However, there are no randomised controlled studies comparing outpatient care with inpatient care, particularly with emphasis on the patients’ perception of symptom relief and their ability to return to normal daily activities and work.
Methods and analysis
This is a prospective, randomised, controlled, parallel group non-inferiority trial comparing the traditional hospital surveillance (inpatient, patients staying in the hospital for 1–3 nights after surgery) with outpatient care (discharge on the day of the surgery, usually within 6–8 hours after procedure) in patients who have undergone anterior cervical decompression and fusion procedure. To determine whether early discharge (outpatient care) is non-inferior to inpatient care, we will randomise 104 patients to these two groups and follow them for 6 months using the Neck Disability Index (NDI) as the primary outcome. We expect that early discharge is not significantly worse than the current care in terms of change in NDI. Non-inferiority will be declared if the mean improvement for outpatient care is no worse than the mean improvement for inpatient care, by a margin of 17.3%. We hypothesise that a shorter hospital stay results in more rapid return to normal daily activities, shorter duration of sick leave and decreased secondary costs to healthcare system. Secondary outcomes in our study are arm pain and neck pain using the Numeric Rating Scale, operative success (Odom’s criteria), patient’s satisfaction to treatment, general quality of life (EQ-5D-5L), Work Ability Score, sickness absence days, return to previous leisure activities and complications.
Trial registration number NCT03979443.